2004
DOI: 10.1038/sj.onc.1208008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NF-κB-responsive gene BTG2 is aberrantly regulated in breast cancer

Abstract: BTG2, a p53-inducible antiproliferative gene, is stimulated in breast cancer cells by activation of nuclear factor kappa B (NF-jB). In rat mammary glands, BTG2 is expressed in epithelial cells and levels decreased during pregnancy and lactation but recovered during involution. Estrogen and progestin suppress BTG2 expression, suggesting that these steroids, which stimulate proliferation and lobuloalveolar development of mammary epithelial cells, may downregulate BTG2 in the mammary gland during pregnancy. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 42 publications
9
83
0
Order By: Relevance
“…Identification of BTG2 as a transcriptional target of p53 (Cortes et al, 2000), and as a key mediator of p53-dependent cellular transformation of mouse and human fibroblasts transduced with oncogenic Ras (Boiko et al, 2006), suggests that it has an important role in inhibiting tumorigenesis. This is consistent with the repression of BTG2 expression in several human tumors including the breast, thymus, prostate and kidney (Lim et al, 1995;Ficazzola et al, 2001;Kawakubo et al, 2004Kawakubo et al, , 2006Struckmann et al, 2004). Moreover, expression of BTG2 in a mouse model for medulloblastoma suppressed the formation of tumors (Farioli-Vecchioli et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Identification of BTG2 as a transcriptional target of p53 (Cortes et al, 2000), and as a key mediator of p53-dependent cellular transformation of mouse and human fibroblasts transduced with oncogenic Ras (Boiko et al, 2006), suggests that it has an important role in inhibiting tumorigenesis. This is consistent with the repression of BTG2 expression in several human tumors including the breast, thymus, prostate and kidney (Lim et al, 1995;Ficazzola et al, 2001;Kawakubo et al, 2004Kawakubo et al, , 2006Struckmann et al, 2004). Moreover, expression of BTG2 in a mouse model for medulloblastoma suppressed the formation of tumors (Farioli-Vecchioli et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
“…We had previously shown that loss of BTG2 protein in breast cancer is associated with higher tumor grade and size and overexpression of the cyclin D1 protein (Kawakubo et al, 2004(Kawakubo et al, , 2006. Analysis of several Oncomine microarray data sets corroborated these findings and revealed a strong correlation between decreased BTG2 expression in breast cancer and characteristics of tumor progression.…”
Section: Discussionmentioning
confidence: 55%
“…A loss of nuclear BTG2 expression is observed in ERα positive human breast tumors (Kawakubo et al, 2006), and an inverse correlation between breast tumor size and BTG2 expression has also been demonstrated (Kawakubo et al, 2006). BTG2 mRNA levels have been shown to be decreased by E2 and progestins in MCF-7 and T-47D breast cancer cells, respectively (Kawakubo et al, 2004). To the best of our knowledge this is however the first report on FGF-mediated repression of Btg2.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, BTG2 /TIS21 expression is very low or undetectable in human breast cancer cell lines, compared with non-tumorigenic mammary epithelial cell, however, it is stimulated in breast cancer cells by the activation of nuclear factor kappa B. In rat mammary glands, the BTG2 /TIS21 expression in epithelial cells is decreased during pregnancy and lactation, but recovered during involution (Kawakubo et al 2004), suggesting that estrogen and progestin may downregulate BTG2 /TIS21 in the mammary gland during pregnancy. These data indicate that the deregulation of BTG2 /TIS21 early at the tumorigenic process may also be an important step in the development of mammary tumors.…”
Section: Potential Function Referencementioning
confidence: 98%
“…Suppression of BTG2 /TIS21 mRNA in the mammary gland during pregnancy and lactation and treatment of the cells with estrogen and progestin stimulate cyclin D1 expression. Furthermore, ectopic expression of BTG2 /TIS21 inhibits breast cancer cell growth by arresting the cells at G1 phase, and the effect is reversed by cyclin D1 (Kawakubo et al 2004). Therefore, TIS21 /BTG2//PC3 induces the cell cycle arrest through at least two pathways: cyclin D1 and cyclin E. The latter becomes prominent when the function of pRB and possibly other cell cycle regulators such as p53 are impaired.…”
Section: Tis21mentioning
confidence: 99%